Relation of metabolic syndrome with endometrial pathologies in patients with abnormal uterine bleeding - Ozdemir, Suna; Batmaz, Gonca; Ates, Seda; ATEŞ, SEDA; Celik, Cetin; Incesu, Feyzanur; Peru, Celalettin (My University, 2015)
Purpose: We aimed to investigate the association of metabolic syndrome and metabolic risk factors with endometrial hyperplasia and carcinoma among women with abnormal uterine bleeding (AUB).